Frequencies of secretors and non-secretors of ABH group substances among 1, 000 alcoholic patients. Issue 5681 (22nd November 1969) - Camps, F. E.; Dodd, Barbara E.; Lincoln, P. J.
Abstract : The ABO blood group and secretor status of 1, 000 alcoholic patients has been determined. The patients were drawn from large alcoholic units in the London area together with several small units, including rehabilitation centres, nd 127 were from Aberdeen. The findings have been compared with appropriate controls which take into account the ethnic origin of the patients in the series. A striking disturbance of the secretor/non-secretor ratio among group A patients compared with the controls is observed. There is an increase in group A non-secretors, which is almost exactly balanced by a loss of group A secretors so that the overall frequency of the group A phenotype is not disturbed. It is difficult to find an acceptable explanation for these results.